(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of multifunctions called upper quasi θ(τ_1,τ_2)-continuous multifunctions and lower quasi θ(τ_1,τ_2)-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper quasi θ(τ_1,τ_2)-continuous multifunctions and lower quasi θ(τ_1,τ_2)-continuous multifunctions are established.